Human Rights Research: Three Contributions From the Institute of Latin American Studies - Barrera Rivera, Dan Abner (2018)
The purpose of this article is to show how academic research on human rights is done, based on three works carried out at the Institute of Latin American Studies of the National University of Costa Rica, in the Master's Degree program in Human Rights and Education for Peace. The topics addressed are the representation of Costa Rican peasants in the media, violence against trans women in public places, and spaces for integral well-being for LGBTIQ people. Four main elements stand out from these investigations: the pertinence of the subjects; the methodology used to investigate; the theoretical categories present in the inquiries; and the results obtained. Based on these elements, and with the objective of making them visible, a hermeneutic reading of the five hundred and fifty pages that add up to the three works was conducted. In conclusion, these research works present originality, creativity, and depth; they are pioneering works in their respective subjects and represent a contribution to the production of knowledge in the area of human rights.